A re-appraisal of the spatial distribution of single and multi-moat prehistoric sites in Northeast Thailand. (September 2017) - Scott, Glen; O'Reilly, Dougald
Abstract: The circular, moated sites of Northeast Thailand are among the most readily distinguished archaeological features in prehistoric Southeast Asia via aerial survey. Seminal work analysing the distribution of these sites was undertaken by Moore, Welch and McNeill in the late 1980s and early 1990s. These studies sought to analyse spatial clustering and the relationship between elevation with site size and density. Recent research by the authors has led to the discovery of further moated sites in Northeast Thailand thereby potentially affecting the conclusions reached by Moore, Welch and McNeill. This paper revisits Moore's original nearest neighbor analysis, including newly identified sites. Moore had concluded there was a random distribution of moated sites in her study area but the updated research clearly demonstrates clustering of moated sites in the Khorat Basin. The elevation at which settlements are located is also revealed to be correlated to the size of the sites and the density of distribution of sites in the study area. The authors argue that these results may be due to the reduced availability of water at higher elevations a finding which correlates strongly with recent evidence which links patterns of precipitation to the distribution and density of sites on the Khorat Plateau. These findings may also have implications for the interpretation of socio-political organisation of Iron Age sites in Northeast Thailand.